Elektronischer Handel und Steuerstaat: neue Herausforderungen in der neuen Ökonomie - Jürgen Stehn (Zeitschrift für Wirtschaftspolitik, 2003)
– The article analyses the reform pressure on turnover and income tax systems stemming from the upsurge of crossborder B2C and B2B electronic commerce. It shows that the main challenge of the New Economy is to effectively cope with B2C international trade in digital online goods and services. However, most approaches to turnover taxation discussed in the literature give rise to several surveillance, efficiency, incentive, and identification problems. As a consequence, there seem to be only two appropriate approaches to deal with the special characteristics of international trade in cyberspace, the country-of-origin principle combined with a taxation of digital goods and services at the physical location of producers, and the community principle in combination with a withholding tax (WITHVAT). Moreover, it is shown that the special characteristics of the New Economy lead to a fiercer international tax competition with regard to income taxation.
Keywords: H21; F15; 330; E-Business; Steuersystem; Außensteuerrecht; Steuerwettbewerb; International; EU-Staaten